Manning, J.G. The last Pharaos. Egypt under the Ptolemies, 305-30 BC. Princeton (New Jersey), Oxford: Princeton University Press, 2010 - Goñi Zabalegui, Amaia (ARYS. Antigüedad: Religiones y Sociedades, 2020)
--